Clinico-Immunological Status and Neurocognitive Function of Perinatally Acquired HIV-Positive Children on cART: A Cross-Sectional Correlational Study in South Africa - Lentoor, Antonio G. (Frontiers in Neurology, 2020)
Despite the undisputed benefits of combination antiretroviral therapy (cART), perinatally acquired HIV (PHIV) children on treatment often presents with a spectrum of neurological deficits known as HIV-associated neurocognitive impairment. Even higher CD4 cell count does not seem to prevent the development of neurocognitive impairment in children with PHIV. While CD4 cell count has shown to have the greatest prognostic value, its association with neurocognitive abilities remains to be clarified. This study aimed at determining the correlation between plasma CD4+ lymphocyte and neurocognitive function in children with PHIV on cART. In total, 152 purposively recruited hospital based sample of children with PHIV on cART, aged 3 years to 7 years 6 months (mean age 63.13 months) underwent neurocognitive assessment using the Wechsler Preschool and Primary Scale of Intelligence (WPPSI-III). Immunological status of each child was based on the plasma CD4+ lymphocyte levels. The mean CD4+ lymphocyte cell count at the time of neurocognitive assessment was 1259.85 cell/mm3 (mean range: 139 – 2717), with significant age difference on CD4+ lymphocyte count levels [F (2,149) = 13.58, p = .000]. CD4+ lymphocyte counts was significantly correlated with subdomains of neurocognitive function scores of task that measures working memory, processing speed and perceptual reasoning. Global cognitive ability (FSIQ) had no significant association with immunological status of the children. The findings supports an association between immunological status of PHIV infection and executive function task. These neurocognitive faculties are critical for learning; school readiness and success in early childhood; and ultimately treatment adherence in adolescence. The need for early identification of neurodevelopment deficits in children, even when on cART, is crucial since early psychosocial and neurorehabilitative interventions can lead to better outcome for children with PHIV.